Experimental analysis and simulation of catalytic converters - Mohiuddin, A. K. M. (IIUM Press, 2011)
The purpose of this chapter is to present the results of an experimental study ofthe performance of ceramic monolith three-way catalytic converters (TWCC) employed in automotive exhaust lines for the reduction of gasoline emissions. Two ceramic converters of different cell density, substrate length, hydraulic channel diameter and wall thickness were investigated. After completing the test, the converters were cut to extract the substrate or 'honeycomb' inside the housing and being analyzed for microstructure and materials composition using Scanning Electron Microscopy (SEM) and Energy Dispersive Analysis (EDX). Simulation program using commercial computational fluid dynamics (CFD) software packages, GAMBIT and FLUENT 6.1 was used to verify experimental results.